#DescriminalizaSTF: um manifesto antiproibicionista ancorado no empírico - (:unkn) unknown (Universidade Federal do Pampa, 2012)
The study describes how crimes of drug possession for personal consumption are managed by the Special Criminal Courts in the city of Porto Alegre. The research comprises the analysis of 105 lawsuits throughout the year of 2009 in the state capital. The methodological procedures adopted included the attendance to court hearings, interviews and some ethnographic incursions. Inadequate management in cases of problematic and non-problematic consumption was observed. The article attempts, thus, to present anti-prohibition arguments that are able to sensitize the Judiciary in the implementation of the (judicial) descriminalization process, mainly due to the fact that this issue was granted the status of general repercussion by the Supreme Court.
#DecriminalizeSTF: an anti-prohibitionist manifesto anchored in the empirical
Keywords: Drogas; Direito penal; Descriminalização; Antiproibicionismo; Drugs; Criminal law; Decriminalization; Anti-prohibitionism; CNPQ::CIENCIAS SOCIAIS APLICADAS